2007
DOI: 10.1016/j.jml.2007.06.005
|View full text |Cite
|
Sign up to set email alerts
|

The effects of visual beats on prosodic prominence: Acoustic analyses, auditory perception and visual perception

Abstract: General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.-Users may download and print one copy of any publication from the public portal for the purpose of private study or research-You may not further distribute the material or use it for any profit-making activity or commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
291
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 322 publications
(312 citation statements)
references
References 72 publications
(82 reference statements)
16
291
0
5
Order By: Relevance
“…The emphatic function of head nods has also been observed in perception studies. It has been found that eyebrow movements and head nods help listeners to perceive prominent events in speech (House et al, 2001;Krahmer and Swerts, 2007) and facilitate the recognition of prosodic contrastive focus (Dohen and Loevenbruck, 2004;Prieto et al, 2015). It has been proposed that the temporal patterns of the gesturespeech integration can be influenced by semantic and pragmatic reasons (e.g., Bergmann et al, 2011;Esteve-Gibert et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The emphatic function of head nods has also been observed in perception studies. It has been found that eyebrow movements and head nods help listeners to perceive prominent events in speech (House et al, 2001;Krahmer and Swerts, 2007) and facilitate the recognition of prosodic contrastive focus (Dohen and Loevenbruck, 2004;Prieto et al, 2015). It has been proposed that the temporal patterns of the gesturespeech integration can be influenced by semantic and pragmatic reasons (e.g., Bergmann et al, 2011;Esteve-Gibert et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…1). Equating the audio across all conditions was important, to control for subtle differences in how producing gestures and actions might alter the acoustic properties of the accompanying speech (Krahmer and Swerts 2007). Because the lips were digitally obscured, it was not a problem to temporally align the speech with the visual gestures and actions.…”
Section: Methodsmentioning
confidence: 99%
“…Eyebrow movements may function as a question marker in French (Purson et al, 1999), even when they are not necessarily coordinated with fundamental frequency changes (Cavé et al, 1996). The same visual cue also has a significant effect on the perception of focus (Krahmer et al, 2002) and prominence , 2006, 2008Krahmer & Swerts, 2007) in Dutch, and may help to distinguish between specific sentence types and pragmatic meanings across languages, such as between Dutch and Catalan (Borràs-Comes & Prieto, 2011;Borràs-Comes et al, 2014;Crespo-Sendra et al, 2013). For instance, Crespo-Sendra et al (2013) have shown that Catalan participants rely more on visual cues than Dutch participants in order to perceive the contrast between neutral and focused yes-no questions, and that this is related to the kind/richness of the respective intonational cues (Catalan speakers use the same intonational contour for both pragmatic meanings, with a different pitch range, whereas Dutch speakers use different intonational contours).…”
Section: Introductionmentioning
confidence: 99%